KEDUDUKAN JANDA TANPA MEMILIKI KETURUNAN DALAM PUTUSNYA PERKAWINAN JUJUR KARENA KEMATIAN PADA MASYARAKAT BATAK TOBA KRISTEN - CITRA BAKTI PANGARIBUAN (PREMISE LAW JURNAL, 2016)
The right to wealth as inheritance of a husband that should be owned by a widow sometimes not hold to due  a widow indeed someone from outside that once presented into husband kinship under marriage reasonable in relation. It is noted the existence of a widow without having any children against inheritance wealth of husband is not assured, so there is no legal surety and it is unfair to widow. In marriage by Christian of Batak Toba people, about the inheritance, the community hold honest marriage in which  is highly decided by clanship paternally. The existence of a widow without any children for Batak Toba community in a honest marriage is not referred as heirs against the late husband but in judged of the late her-husband clanship, settled a widow as long as life is allowable with right to have daily necessity, so for the wealth inheritance of her husband could be just as source of daily economy to survive only. Keywords : Widow, Honest marriage, Christian Toba Batak Toba Community